1996
DOI: 10.1073/pnas.93.12.5980
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of sleep mediated by the A2a-adenosine receptor and possible involvement of this receptor in the sleep induced by prostaglandin D2 in rats.

Abstract: The publication costs of this article were defrayed in part by page charge payment. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C. §1734 solely to indicate this fact.Hypnogenic effects of adenosine were shown by its intracerebroventricular administration in fowls (4) and dogs (5). Subsequently, the effects of adenosine and its analogues on sleep-wake activities were studied in rats by . Recently, Rainnie et al. (10) suggested the cholinergic neurons of the mesopontine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(94 citation statements)
references
References 22 publications
(16 reference statements)
1
93
0
Order By: Relevance
“…Under pentobarbital anesthesia (50 mg/kg, i.p. ), rats underwent surgery for implantation of electrodes for EEG and EMG recordings and placement of a guide cannula for the microdialysis probe as described (35,36). Brief ly, a guide cannula (outer diameter, 0.6 mm) with an in-dwelling stylet was directed stereotaxically into the TMN.…”
Section: Electroencephalogram (Eeg) and Electromyogram (Emg) Recordingsmentioning
confidence: 99%
“…Under pentobarbital anesthesia (50 mg/kg, i.p. ), rats underwent surgery for implantation of electrodes for EEG and EMG recordings and placement of a guide cannula for the microdialysis probe as described (35,36). Brief ly, a guide cannula (outer diameter, 0.6 mm) with an in-dwelling stylet was directed stereotaxically into the TMN.…”
Section: Electroencephalogram (Eeg) and Electromyogram (Emg) Recordingsmentioning
confidence: 99%
“…The stimulant effects of caffeine on the central nervous system at doses obtained through normal human consumption are due to caffeine's ability to antagonize adenosine receptors (Fredholm et al, 1999). Numerous reports have corroborated that adenosine is a neuromodulator that is involved in sleep regulation Benington et al, 1995;Porkka-Heiskanen et al, 1997;Radulovacki et al, 1982Radulovacki et al, , 1985Satoh et al, 1996Satoh et al, , 1999Scammell et al, 2001;Schwierin et al, 1996;Strecker et al, 2000;Ticho and Radulovacki, 1991;Urade et al, 2003). It has recently been proposed that in humans, caffeine mimics the effects of a reduction in sleep homeostasis during prolonged wakefulness (Landolt et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, we previously showed that a PGD 2 or A 2A R agonist suppresses the histaminergic system (12,13,29) and increases both NREM and REM sleep (4,11). For example, an A 2A R agonist (2 pmol/min) increased slow-wave sleep (NREM sleep) by 71% and paradoxical sleep (REM sleep) by 96% in rats (11), whereas an A 1 R one at 1.5 nmol/side increased NREM sleep by 3.1-fold but did not change the amount of REM sleep at all (Fig. 2C).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have shown that PGD 2 is involved in both circadian (6,7) and homeostatic regulation of sleep (8). Further studies on the molecular mechanisms of sleep-wake regulation by PGD 2 demonstrated that PGD 2 is produced by the action of lipocalin-type PGD synthase dominantly expressed in the leptomeninges (9), binds with PGD receptors (DPRs) exclusively localized in the arachnoid membrane of the basal forebrain (BF) (10), and promotes sleep through adenosine acting at adenosine A 2A receptors (A 2A R's) (11), followed by activation of sleep-active neurons in the ventrolateral preoptic (VLPO) area (12,13). The somnogenic effect of PGD 2 is mimicked by an A 2A R agonist, but not by an adenosine A 1 receptor (A 1 R) one, and is blocked by an A 2A R antagonist (11).…”
mentioning
confidence: 99%